The Effect of Leadership and Motivation on Employee Performance at the Tamansari District Office, West Jakarta Administration - Erlita Kurniawaty; Subarto Subarto (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The purpose of this study was to determine the effect of leadership on performance, the influence of leadership on performance, and the influence of leadership and motivation together on employee performance at the Tamansari District Office, West Jakarta. The research method used in this research is descriptive with a quantitative approach, namely by describing the condition of the respondents and research variables. The population in this study were all employees at the Tamansari District Office, West Jakarta. The sample used was 128 respondents with a simple random sampling technique using the Slovin formula. The data analysis technique uses the Validity Test, Reliability Test, Classical Assumption Test, and Multiple Regression through the Coefficient of Determination (R2), t-test, and F-test. The hypothesis test of the results of this study is that leadership has a positive and significant effect on employee performance by 45%. Partially tested the hypothesis obtained t count > t table or (10.133 > 1.657), so that HO is rejected and H1 is accepted, meaning that there is a positive and significant influence between leadership and on the performance of employees at the Tamansari District Office, West Jakarta. Motivation has a positive and significant effect on employee performance by 45.7%. Partially test the hypothesis obtained t arithmetic > t table or (10.261 > 1.657) so that Ho is rejected and H2 is accepted, meaning that there is a positive and significant influence between motivation on employee performance at the Tamansari District Office, West Jakarta. Simultaneous hypothesis testing of leadership and motivation has a positive and significant effect on employee performance with a coefficient of determination of 53.6%, while other factors influence the remaining 46.4%. The calculated F value obtains hypothesis testing> F table or (105.298 > 2.680); thus, Ho is rejected, and H3 is accepted. It means that there is a simultaneous positive and significant influence between leadership and motivation on employee performance at the Tamansari District Office, West Jakarta City